No child is an island – The life situation before and during treatment for children exposed to family violence. Issue 2 (6th May 2022) - Onsjö, Marja; Strand, Jennifer; Axberg, Ulf
Compelling evidence indicates that child maltreatment is a risk factor for developing serious psychopathology. Trauma-focused treatment has been found to be effective, but not all children benefit from it. Interventions that consider multiple aspects of treatment that could improve the efficacy need to be developed. The present study explored how children exposed to family violence described their life situation before and during their contact with the child and adolescent mental health service. Thirteen children and adolescents were interviewed and we analysed the material using thematic analysis. Several of the participants reported continued violence, conflict and insecurity at home, in school and in other contexts. These results indicate how important it is never to assume that because children exposed to family violence are in treatment, they are safe in their homes. Interventions should therefore include continuous assessment of ongoing victimization and safety planning, considering children, not as isolated units, but in the context of complex life situations in which their well-being is affected by their parents, siblings and friends.